Estudos sobre a síntese da (+)-nootkatona a partir de (+)-valenceno utilizando-se foto-oxigenações em regime de fluxo contínuo - Constancio, Samuel da Silva (Universidade Federal de São Carlos, 2025)
In this work, the semi-synthesis of (+)-Nootkatone was developed. (+)-Nootkatone is a high-value-added natural product from the terpene family and is used in the flavor, fragrance, and cosmetics industries. The semi-synthesis was carried out through a photooxygenation reaction of naturally sourced (+)-valencene, followed by a Schenck rearrangement, acetylation, and HOAc elimination to afford (+)-nootkatone; the semi-synthetic route was developed in both batch and continuous-flow regimes. In batch, under optimized conditions for all sequential steps, (+)-nootkatone was obtained in 45% overall isolated yield (4 steps, 82% per step). The transition to continuous flow was performed gradually, step by step, aiming at telescoping as much as possible. Under conditions in which photo-oxygenation was carried out in continuous flow, and the remaining steps in batch, (+)-nootkatone was obtained in 40% yield. Subsequently, a tubular steel reactor was attached for the transposition and telescoping of the rearrangement step, affording (+)-nootkatone in 35% yield. Finally, a new tubular stainless-steel reactor was attached to the setup for telescoping the acetylation and elimination steps, yielding (+)-nootkatone in 30% yield (fully telescoped setup). However, it was not possible to scale up this last process using the fully telescoped setup due to technical issues in the final setup stage. Therefore, scale-up was performed using the configuration in which the photooxygenation and Schenck rearrangement steps were operated under continuous flow, while the acetylation/elimination steps were conducted in batch. Under these conditions, 1.2 g of (+)-nootkatone was obtained in 27% overall isolated yield (2 steps in flow and 2 steps in batch, 72% per step).
Studies on the synthesis of (+)-nootkatone from (+)-valencene using continuous flow photo-oxygenation
Keywords: Nootkatona; Fluxo contínuo; Foto-oxigenação; Foto-oxidação; Nootkatone; Continuous flow; Photooxygenation; Photooxidation; CIENCIAS EXATAS E DA TERRA::QUIMICA::QUIMICA ORGANICA::SINTESE ORGANICA; 9. Indústria, Inovação e Infraestrutura